Solution.
(1-x2)y'' - 2xy' + α(α + 1)y = 0
Dividing both sides of the equation by (1-x2) we get differential equation in standard form:
"y''-\\frac{2x}{1-x^2}y'+\\frac{\\alpha \\left(\\alpha +1\\right)}{1-x^2}y=0" ;
p(t) is the coefficient of y' and q(t) is the coefficient of y:
"p\\left(t\\right)=-\\frac{2x}{1-x^2}"
"q\\left(t\\right)=\\frac{\\alpha \\left(\\alpha +1\\right)}{1-x^2}"
To determine the Wronskian we apply Abel's theorem:
"W\\left(y_1,y_2\\right)\\left(x\\right)=C\\cdot e^{\\left(-\\int p\\left(x\\right)dx\\right)}"
"W\\left(y_1,y_2\\right)=C\\cdot e^{\\left(-\\int \\left(-\\frac{2x}{1-x^2}dx\\right)\\right)}"
"W\\left(y_1,y_2\\right)=C\\cdot e^{\\left(-\\int \\left(\\frac{d\\left(1-x^2\\right)}{1-x^2}\\right)\\right)}"
"W\\left(y_1,y_2\\right)=C\\cdot e^{-\\ln \\left|1-x^2\\right|}"
"W\\left(y_1,y_2\\right)=\\frac{C}{\\left|1-x^2\\right|}"
when W(0) = 1, we will get:
"1=\\frac{C}{\\left|1-0\\right|}"
C = 1, thus:
"W\\left(y_1,y_2\\right)=\\frac{1}{\\left|1-x^2\\right|}"
Answer: W = 1 / |1 - x2|
Comments
Leave a comment